MEMBANGUN EKONOMI KREATIF MELALUI OLAHAN EMPING BUTTER COOKIES UNTUK PENINGKATAN NILAI JUAL PRODUK MELINJO - Hany Azza Umama; Meassa Monikha Sari; Puteri Puspa Larasati; Titi Rohayati; Reynaldi Zesar; Rexsy Nugraha (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The main agriculture product in the Bantar Panjang Village is melinjo seeds which mostly sold by farmers to the small trader at cheap price. The main problem was the overflow of melinjo harvest but the community has no enough knowledge to process it, then its price has not increased yet. Meanwhile, the community interest is only limited to how to process melinjo into emping, but there is no other development. The objective of the community dedication is to build creative community through increase of selling price of melinjo product by developing butter cookies made from emping, by sharing knowledge and skill, and by motivating entrepreneurship interest based on melinjo processing. Beside to increase the creativity of melinjo processing, this activity will also grow entrepreneurship to the community to keep develop melinjo product to become high selling product. This activity can be conducted in the form of training, counseling, and workshop. The main execution of this community dedication is handled by two lecturers and four students. They will be supported by the participant, mostly are housewives in Bantar Panjang Village, Cikuesal Sub-District. The activity consists of three stages: preparation; implementation (training and counseling), and completion (workshop and evaluation). The results are community able to make their own butter cookies made from emping, and they are getting better in the aspect of knowledge to make hygienist food product, packaging, marketing strategy, and home industry product license as well.